Perbedaan Kadar Blood Urea Nitrogen dan Kreatinin Antara Pasien Diabetes Melitus Tipe 2 Terkontrol dan Tidak Terkontrol di RSUD Pasar Rebo Jakarta Timur - Azzahra, Annisha; Putri, Dian Eka (Green Publisher Indonesia, 2025)
Type 2 diabetes mellitus (T2DM) is associated with a risk of microvascular complications, including diabetic nephropathy. Glycemic status is determined through glycated hemoglobin (HbA1C) measurements, where levels below 7% classify diabetes as controlled, and levels of 7% or higher indicate uncontrolled diabetes. Measuring blood urea nitrogen (BUN) and creatinine is essential for determining kidney function. This study aims to analyze the differences in BUN and creatinine levels between controlled and uncontrolled T2DM patients. A cross-sectional study was conducted using secondary data from the medical records of outpatient T2DM patients at the Internal Medicine Clinic of Pasar Rebo General Hospital, East Jakarta, from January to December 2024. Subjects were divided into controlled and uncontrolled diabetes groups based on HbA1C values, with inclusion criteria consisting of patients aged 50–59 years who had been diagnosed with T2DM within the past five years. BUN data were obtained by calculating urea x 2.14 (mg/dL). Normality was tested using the Kolmogorov-Smirnov test. Comparative analysis of BUN and creatinine levels between the two groups was performed, with p<0.05 statistically significant. Among the 100 T2DM subjects evaluated at Pasar Rebo General Hospital, 64% were female, and the average age was 56 years. The mean BUN and creatinine levels in the controlled group were 13.5 and 1 mg/dL, while in the uncontrolled group were 13.59 and 1.04 mg/dL. Analysis using an independent comparison test showed that BUN and creatinine levels were not significantly different in the controlled group (p = 0.93) nor in the uncontrolled group (p = 0.38). The research revealed that there was no meaningful variation in BUN and creatinine levels between T2DM patients with controlled and uncontrolled glycemic status at Pasar Rebo General Hospital, East Jakarta.